Effect of magnetic field on thermosolutal instability of rotating ferromagnetic fluid under varying gravity field - Pundir, Sudhir Kumar; Nadian, Pulkit Kumar; Pundir, R. (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with the theoretical investigation of the effect of a magnetic field, rotation and magnetization on a ferromagnetic fluid under varying gravity field. To find the exact solution for a ferromagnetic fluid layer contained between two free boundaries, we have used a linear stability analysis and normal mode analysis method.
Keywords: thermosolutal instability; ferromagnetic fluid; rotation; magnetic field; magnetization